2021
DOI: 10.31018/jans.v13i2.2696
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drip and alternate furrow method of irrigation on cotton yield and physical water productivity: A case study from farmers’ field of Bhavnagar district of Gujarat, India

Abstract: With the growing irrigation water scarcity, the researchers and policymakers are more concerned to improve the irrigation water use efficiency at farmers’ field level. The water-saving technologies provide greater control over water delivery to the crop root zone and reduce the non-beneficial evaporation from the crop field. Water productivity is an important concept for measuring and comparing water use efficiency. The present study tried to estimate the irrigation water use and physical water productivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It has been proven to increase yields of crops with less water use. Drip irrigation is suggested for different crops including cotton, wheat, gram, soybean and sesame [33,34]. Drip irrigation is widely used for growing a variety of vegetables also, including tomatoes, peppers, cucumbers, and lettuce especially in protected structures like greenhouses [35].…”
Section: Drip Irrigationmentioning
confidence: 99%
“…It has been proven to increase yields of crops with less water use. Drip irrigation is suggested for different crops including cotton, wheat, gram, soybean and sesame [33,34]. Drip irrigation is widely used for growing a variety of vegetables also, including tomatoes, peppers, cucumbers, and lettuce especially in protected structures like greenhouses [35].…”
Section: Drip Irrigationmentioning
confidence: 99%
“…The results of scientific research conducted by many scientists [1][2][3][4][5][6][7][8] showed the feasibility of using water treated with a magnetic field to irrigate crops and wash saline lands. In this direction, numerous studies were carried out by the following scientists: Singh O. P., Feng J., Novikova A.V., Kasymbetova S.A., Zhou B., Wei K., Zhang J., Bhattarai S., Shi K., Kong J., Yadollahi A. H., Yesuf H. M.…”
Section: Introductionmentioning
confidence: 99%